New neolignan glycoside from the root of Aralia echinocaulis Hand. -Mazz. Issue 9 (3rd May 2017) - Li, Yunzhi; Cheng, Hui; Yue, Ren; Duan, Mengmeng; Liu, Mingdong
Abstract: A phytochemical investigation was carried out to the root of Aralia echinocauis, and a new neolignan glycoside, 3-3, 5-dimethoxy-4β-d -Glucopyranoside-2-[3-(3-β-d -Glucopyranoside-4-methoxy-phenyl)-allyl]-phenyl-prop-2-en-1-ol (1 ), together with a known saponin, araliasaponin II (2 ) for the first time was obtained . The chemical structure of compound1 was identified mainly by the analysis of NMR including 1D and 2D NMR in combination with High Resolution Electrospray Ionisation Mass (HR-ESI-MS). This paper herein describes the isolation and structural elucidation of compound1 . Abstract :